An Examination of Long‐Term Abnormal Stock Returns and Operating Performance Following R&D Increases - Eberhart, Allan C.; Maxwell, William F.; Siddique, Akhtar R. (Journal of Finance, 2004)
ABSTRACT We examine a sample of 8,313 cases, between 1951 and 2001, where firms unexpectedly increase their research and development (R&D) expenditures by a significant amount. We find consistent evidence of a misreaction, as manifested in the significantly positive abnormal stock returns that our sample firms' shareholders experience following these increases. We also find consistent evidence that our sample firms experience significantly positive long‐term abnormal operating performance following their R&D increases. Our findings suggest that R&D increases are beneficial investments, and that the market is slow to recognize the extent of this benefit (consistent with investor underreaction).